1969
DOI: 10.1099/00221287-55-3-433
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Cutaneous Lipophilic Diphtheroids

Abstract: SUMMARYSixty lipophilic diphtheroids (LD) isolated from human skin were characterized by a variety of morphological, biochemical, physiological and nutritional tests. The LD strains were tentatively placed into six fermentative groups and one non-fermentative group. Most LD strains required amino nitrogen, others required vitamins plus amino acids for growth. Nine LD isolates initiated growth with ammonia as a sole nitrogen source. Urea and nitrate were not utilized. A total of 149 cutaneous bacteria were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

1969
1969
1995
1995

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 13 publications
2
35
0
2
Order By: Relevance
“…Despite much research dealing with the sterilizing properties of skin and its vulnerability to infection, surprisingly little attention has been given to studying the ecology of the resident cutaneous bacteria (Marples, 1965). There appear to be many more lipophilic corynebacteria on human skin than was once thought (Smith, 1969). Information on the distribution and types of these bacilli relative to cocci is lacking as is knowledge of ecological factors that may regulate these two major groups of skin bacteria.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite much research dealing with the sterilizing properties of skin and its vulnerability to infection, surprisingly little attention has been given to studying the ecology of the resident cutaneous bacteria (Marples, 1965). There appear to be many more lipophilic corynebacteria on human skin than was once thought (Smith, 1969). Information on the distribution and types of these bacilli relative to cocci is lacking as is knowledge of ecological factors that may regulate these two major groups of skin bacteria.…”
Section: Introductionmentioning
confidence: 97%
“…The sources of the reference strains used in this study were previously reported (Smith, 1969). This group included the following: American Type Culture Collection (ATCChListeria monocytogenes ATCC 153 I 3, Kurthia zopJii Md., U.S.A. : C. granulosum 3024B, C. diphtheroides 2764, C. liquefaciens 3 0 4 4~, C. pyogenes 6 3 7~ and C. lyrnphophilium PREVOT.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to classify these organisms on the basis of biochemical characteristics have been undertaken. Smith (26) separated lipophilic diphtheroids isolated from the skin into seven taxonomic groups, while Furness et al reported (9) ten phenotypic groups for such coryneform bacteria isolated from nonspecific urethritis corresponding to five pathogenic types ("Corynebacterium genitalium") and five saprophytic types ("Corynebacterium pseudogenitalium") of the urogenital tract (8). Analysis of their cell walls revealed the presence of arabinose, galactose, diaminopimelic acid, and corynomycolic acids (7), which are characteristic of the genus Corynebacten'um.…”
mentioning
confidence: 99%
“…C. xerosis (NCTC no. 7243) was not lipophilic and did not reduce nitrate, although Smith (1969a) found that the three reference strains of c. xerosis (ATCC strains) he studied all reduced nitrate; C. striatum (NCTC no. 764) did reduce nitrate and Smith could differentiate between these two species only by sugar fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…10288). Breed et al (1957) state that C. bovis does not decompose carbohydrates though Smith (1969a) found that three reference strains produced acid from glucose, fructose, and galactose and one did so from maltose. C. minutissimum and C. bovis could be differentiated by other tests, for example sucrose fermentation and urease produc- Bold numbers indicate areas where group is significantly more common than at other sites.…”
Section: Resultsmentioning
confidence: 99%